2023
DOI: 10.3390/ph16030337
|View full text |Cite
|
Sign up to set email alerts
|

TLR4/Inflammasomes Cross-Talk and Pyroptosis Contribute to N-Acetyl Cysteine and Chlorogenic Acid Protection against Cisplatin-Induced Nephrotoxicity

Abstract: Background: Cisplatin (Cp) is an antineoplastic agent with a dose-limiting nephrotoxicity. Cp-induced nephrotoxicity is characterized by the interplay of oxidative stress, inflammation, and apoptosis. Toll-4 receptors (TLR4) and NLPR3 inflammasome are pattern-recognition receptors responsible for activating inflammatory responses and are assigned to play a significant role with gasdermin (GSDMD) in acute kidney injuries. N-acetylcysteine (NAC) and chlorogenic acid (CGA) have documented nephroprotective effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…The benefits of G. biloba and its preparations in the prevention and treatment of cardiovascular diseases mainly derive from the effective chemical components such as flavonoids and terpenoid lactones. In this study, through data mining and network pharmacology analysis of relevant literature, we found that the organic acid components (protocatechuic acid, caffeic acid, chlorogenic acid, and gallic acid), flavonoid components (quercetin‐3‐O‐glucoside, quercetin‐3‐O‐rutinoside, kaempferol‐3‐O‐rutinoside, kaempferol‐3‐O‐glucoside, isorhamnetin‐3‐O‐rutinoside, isorhamnetin‐3‐O‐glucoside, apigenin‐7‐O‐glucoside, and apigenin), and terpenoid lactones (bilobalide, ginkgolide A, ginkgolide B, ginkgolide C, and ginkgolide J) had different effects such as anti‐inflammatory and anti‐oxidative activities, protecting the nervous system, changing blood rheology, and so on 22–50 . These components may be the potential active substance basis of its anti‐IS effect, so they were included in the scope of analysis and investigation of the active components of GBE against IS.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The benefits of G. biloba and its preparations in the prevention and treatment of cardiovascular diseases mainly derive from the effective chemical components such as flavonoids and terpenoid lactones. In this study, through data mining and network pharmacology analysis of relevant literature, we found that the organic acid components (protocatechuic acid, caffeic acid, chlorogenic acid, and gallic acid), flavonoid components (quercetin‐3‐O‐glucoside, quercetin‐3‐O‐rutinoside, kaempferol‐3‐O‐rutinoside, kaempferol‐3‐O‐glucoside, isorhamnetin‐3‐O‐rutinoside, isorhamnetin‐3‐O‐glucoside, apigenin‐7‐O‐glucoside, and apigenin), and terpenoid lactones (bilobalide, ginkgolide A, ginkgolide B, ginkgolide C, and ginkgolide J) had different effects such as anti‐inflammatory and anti‐oxidative activities, protecting the nervous system, changing blood rheology, and so on 22–50 . These components may be the potential active substance basis of its anti‐IS effect, so they were included in the scope of analysis and investigation of the active components of GBE against IS.…”
Section: Discussionmentioning
confidence: 95%
“…Quercetin‐3‐O‐rutinoside, kaempferol‐3‐O‐rutinoside, kaempferol‐3‐O‐glucoside, and isorhamnetin‐3‐O‐rutinoside can inhibit the PI3K‐Akt, NF‐κB, and other signalling pathways and reduce cardiovascular and cerebrovascular injuries 37–44 . The ingredients such as caffeic acid, protocatechuic acid, gallic acid, bilobalide, ginkgolide A, quercetin‐3‐O‐rutinoside, kaempferol‐3‐O‐rutinoside, kaempferol‐3‐O‐glucoside, and isorhamnetin‐3‐O‐rutinoside also have anti‐oxidative, free radical‐scavenging, and anti‐apoptotic effects 22–50 . Consequently, it was deduced that anti‐inflammatory, anti‐oxidative, anti‐apoptotic, and other activities are the main anti‐IS effects of GBE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In traditional Asian medicinal practices, curcumin has been an extensively employed therapeutic agent attributed to its multifaceted health-promoting characteristics, such as antioxidative, anti-inflammatory, antimutagenic, antimicrobial, and anticancer activities [45] . Being a polyphenol, curcumin exhibits broad biological activity, as it can interact with several cellular signalling pathways, thereby substantiating its extensive health benefits [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] .…”
Section: Unveiling the Therapeutic Potential Of Curcumin In Hepatic W...mentioning
confidence: 99%
“…The cysteine derivative serves as a donor of L-cysteine, which is the building block and the limiting substrate for de novo synthesis of GSH ( 22 ). A large body of evidence has shown that NAC is potentially useful in treatment of various liver and kidney injuries ( 2 , 7 , 13 , 17 , 20 , 35 ).…”
Section: Introductionmentioning
confidence: 99%